2004
DOI: 10.1097/00001665-200411000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing Disorders in Pierre Robin Sequence: Its Correction by Distraction

Abstract: Pierre Robin sequence is characterized by micro-gnathia, glossoptosis, feeding difficulties, and upper respiratory obstruction, which are frequently complicated by bronchial aspiration and pulmonary infection. Gastroesophageal reflux is also common in these patients. To assess the results of mandibular distraction, a study was performed in 18 patients to detect swallowing disorders associated with apnea episodes and gastroesophageal reflux. Polysomnography, barium pharyngoscopy, determination of blood gases, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 17 publications
2
87
1
3
Order By: Relevance
“…It has been observed that DO reduces the need for tracheotomy especially in pediatric patients and allows for early decannulation in patients who previously underwent tracheotomy 14,15 . In addition, oral feeding is significantly improved after DO 16,17 . Surgical intervention using DO in early childhood is a common approach.…”
Section: Discussionmentioning
confidence: 95%
“…It has been observed that DO reduces the need for tracheotomy especially in pediatric patients and allows for early decannulation in patients who previously underwent tracheotomy 14,15 . In addition, oral feeding is significantly improved after DO 16,17 . Surgical intervention using DO in early childhood is a common approach.…”
Section: Discussionmentioning
confidence: 95%
“…Some neonates are not able to be fed orally and necessitates the placement of nasogastric tube 11 . Several theories have been proposed related to this restriction such as glossoptosis preventing the forward positioning of tongue during swallowing and additional lack of sucking and swallowing coordination secondary to airway obstruction in severe patients 26 . Mandibular distraction had also found to be beneficial in means of feeding problems 1,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Mandibular Distraction Osteogenesis (MDO) has been demonstrated to be a safe 3,[11][12][13][14][15][16][17] and effective 3,6,8,12,13,[15][16][17] intervention to relieve airway obstruction in infants with severe RS.…”
Section: Discussionmentioning
confidence: 99%
“…After popularization by McCarthy, 1 MDO was successfully applied to children with RS to relieve affected patients from tracheostomy. [2][3][4] After these initial reports,…”
Section: Mandibular Distraction Osteogenesis (Mdo) Is a Standard Techmentioning
confidence: 99%